Visible-light driven photocatalytic degradation of rhodamine B by Ag/Bi2WO6 heterostructures - Anukorn Phuruangrat (2018)
© 2015 Elsevier B.V. All rights reserved. Ag/Bi < inf > 2 < /inf > WO < inf > 6 < /inf > photocatalysts with different silver loadings were synthesized by hydrothermal process and the reduction of silver by sonochemistry. XRD, TEM and XPS revealed the presence of Ag nanoparticles deposited on orthorhombic Bi < inf > 2 < /inf > WO < inf > 6 < /inf > square nanoplates. The photocatalytic degradation of rhodamine B (RhB) by Ag/Bi < inf > 2 < /inf > WO < inf > 6 < /inf > nanocomposites under visible irradiation showed that the deposited Ag nanoparticles greatly improved the photocatalytic efficiency comparing to pure Bi < inf > 2 < /inf > WO < inf > 6 < /inf > nanocrystallites, with 10 wt% Ag/Bi < inf > 2 < /inf > WO < inf > 6 < /inf > at the highest.